PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN DAN KINERJA KEUANGAN TERHADAP BELANJA MODAL DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2015-2017 - Damar Daru Sukmaji; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine the effect of Local Own Revenue, iscal balance transfers from the central government to regions and Regional Financial Effectiveness Level towards on the capital expenditure at the regencies/municipalities in Central Java Province. The sample used in this study were 35 regencies/municipalities in Central Java Province in 2015-2017.Sampling is done using the purposive sampling method. The test results show that the Local Own Revenue, General Allocation Fund, special allocation fund, Revenue Sharing Fund have a positive and significant effect on capital expenditure while Regional Financial Effectiveness Level have a positive effect but does not have significant effect on capital expenditure. With this result it can be said that the higher the Local Own Revenue, the general allocation fund, the special allocation fund and the Revenue Sharing Fund, the higher the capital expenditure, the hasn’t have signifiicant effect of Regional Effectiveness and the capital expenditure it might be influenced by several other factors.